PENGEMBANGAN MEDIA E-BOOKLET BERBASIS FLIPBOOK MAKER UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SEL - Febby Zilvania Saragih; Gunaria Siagian; Gloria Sirait (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
Learning biology, particularly on the topic of cells, often poses challenges for students due to its abstract nature. In addition, the instructional media commonly used in the classroom remain simple and less interactive, which reduces students’ interest and limits their understanding. This condition affects learning outcomes that tend to be unsatisfactory. This study aims to develop an e-booklet learning media based on flipbook maker and to evaluate its feasibility, students’ responses, and its effect on improving learning outcomes. The research employed the Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The subjects were eighth-grade students of MTs Muhammadiyah 25 Marubun Jaya. Data were collected through expert validation sheets, student response questionnaires, and learning achievement tests. The results indicate that the developed e-booklet achieved an average feasibility score of 90% (categorized as “very feasible”) and received student responses of 88% (categorized as “very good”). Moreover, students’ learning outcomes improved after using the developed media. Therefore, the flipbook maker-based e-booklet is considered effective and feasible to be implemented as an alternative learning medium in biology, particularly in the topic of cells.